The Relationship between Metabolic Parameters, Cardiac Parameters and MIC-1/GDF15 in Obese Children - Yuca, S. A.; Cimbek, E. A.; Şen, Y.; Güvenç, O.; Vatansev, H.; Buğrul, F.; Gün, F.; Oran, B. (Experimental and Clinical Endocrinology & Diabetes, 2017)
Objective: Childhood obesity which is a predictor of adulthood obesity is associated with type 2 diabetes, metabolic syndrome, dyslipidemia, coronary artery diseases and subclinical inflammation. Growth differentiation factor-15, also known as macrophage inhibitory cytokine-1 (MIC-1/GDF15) is a member of the transforming growth factor- β super family and increases during inflammatory states. Adults with obesity have increased serum concentrations of MIC-1/GDF15. MIC-1/GDF15 is associated with cardio metabolic risk in adults.Design: Identification of obese children at higher risk for cardio metabolic complications is important. The relations of MIC-1/GDF15 to parameters of obesity in children have never been studied.Methods: We measured serum MIC-1/GDF15 concentration in obese children by ELİSA and evaluated its relationship with anthropometric, biochemical and echocardiographic parameters.Results: No significant difference in serum MIC-1/GDF15 between normal-weight and obese children was observed. MIC-1/GDF15 was positively correlated with CRP, ALT and aortic dimension when normal-weight and obese children were analyzed together.Conclusions: MIC-1/GDF15 may provide a link between childhood obesity and cardio metabolic complications that will occur in time course. Further work would be required to find out if MIC-1/GDF15 has any role in the early inflammatory, cardiac and metabolic changes in childhood obesity.
Keywords: obesity; MIC-1/GDF15; inflammation; cardiovascular risk management